A complex of U1 snRNP with cleavage and polyadenylation factors controls telescripting, regulating mRNA transcription in human cells - So, Byung Ran (Mol Cell, 2019)
Full-length transcription in the majority of human genes depends on U1 snRNP (U1) to co-transcriptionally suppress transcription-terminating premature 3’-end cleavage and polyadenylation (PCPA) from cryptic polyadenylation signals (PASs) in introns. However, the mechanism of this U1 activity, termed telescripting, is unknown. Here, we captured a complex, comprising U1 and CPA factors (U1–CPAFs), that binds intronic PASs and suppresses PCPA. U1–CPAFs are distinct from U1-spliceosomal complexes; they include CPA’s three main subunits, CFIm, CPSF, and CstF, lack essential splicing factors, and associate with transcription elongation and mRNA export complexes. Telescripting requires U1:pre-mRNA base-pairing, which can be disrupted by U1 antisense oligonucleotide (U1 AMO), triggering PCPA. U1 AMO remodels U1–CPAFs, revealing changes, including recruitment of CPA-stimulating factors, that explain U1–CPAFs’ switch from repressive to activated states. Our findings outline U1 telescripting mechanism and demonstrate U1’s unique role as central-regulator of pre-mRNA processing and transcription.